High-resolution melting-curve (HRM) analysis for C. meleagridis identification in stool samples. (February 2018) - Chelbi, Hanen; Essid, Rym; Jelassi, Refka; Bouzekri, Nesrine; Zidi, Ines; Ben Salah, Hamza; Mrad, Ilhem; Ben Sghaier, Ines; Abdelmalek, Rym; Aissa, Sameh; Bouratbine, Aida; Aoun, Karim
Abstract: Background: Cryptosporidiosis represents a major public health problem. This infection, caused by a protozoan parasite of the genus Cryptosporidium, has been reported worldwide as a frequent cause of diarrhoea. In the immunocompetent host, the typical watery diarrhea can be self-limiting. However, it is severe and chronic, in the immunocompromised host and may cause death. Cryptosporidium spp. are coccidians, which complete their life cycle in both humans and animals. The two species C. hominis and C. parvum are the major cause of human infection. Compared to studies on C. hominis and C. parvum, only a few studies have developed methods to identify C. meleagridis . Aim: To develop a new real time PCR-coupled High resolution melting assay allowing the detection for C. meleagridis, in addition of the other dominant species ( C. hominis and C. parvum ). Methods: The polymorphic sequence on the dihydrofolate reductase gene (DHFR) of three species was sequenced to design primers pair and establish a sensitive real-time PCR coupled to a high-resolution melting-curve (HRM) analysis method, allowing the detection of Cryptosporidium sp. and discrimination between three prevalent species in Tunisia. We analyzed a collection of 42 archived human isolates of the three studied species. Results: Real-time PCR coupled to HRM assay allowed detection of Cryptosporidium, using the new designed primers, and basing on melting profile, we can distinguish C. meleagridis species in addition to C. parvum and C. hominis . Conclusion: We developed a qPCR-HRM assay that allows Cryptosporidium genotyping. This method is sensitive and able to distinguish three Cryptosporidium species. Highlights: We sequenced the polymorphic sequence on the dihydrofolate reductase gene (DHFR) of three species of Cryptosporidium. We designed new primers pair. We developed a real time PCR coupled High-resolution melting-curve (HRM) analysis. The new PCR-HRM allowing the detection for C. meleagridis, in addition of C. hominis and C. parvum.